2021
DOI: 10.3389/fpsyg.2021.694057
|View full text |Cite
|
Sign up to set email alerts
|

Job Insecurity and Job Performance: A Serial Mediated Relationship and the Buffering Effect of Organizational Justice

Abstract: The study aimed to extend the current knowledge of the relationship between job insecurity and performance. In line with traditional stress theories, work-family and burnout were hypothesized as serial mediators of the negative link between job insecurity and job performance. Also, the current study hypothesized that the association between job insecurity and the mediators [i.e., Work-family conflict (WFC) and burnout] could be buffered by perceived organizational justice among employees. Therefore, we empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 86 publications
2
12
0
Order By: Relevance
“…Previous research has shown that employees with more positive emotions exhibit more energy and passion and are more actively involved in their organisations, leading to higher job performance (Macey & Schneider, 2008). Some studies have reported the relationship between organisational justice and job performance (de Angelis et al, 2021;Otto & Mamatoglu, 2015;Wang et al, 2015), there is no in-depth analysis of the role of professional identity and emotional labour in the relationship, especially for clinical nurses. Therefore, the present study aimed to examine the relationship among nurses' perceived organisational justice, professional identity, emotional labour and job performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that employees with more positive emotions exhibit more energy and passion and are more actively involved in their organisations, leading to higher job performance (Macey & Schneider, 2008). Some studies have reported the relationship between organisational justice and job performance (de Angelis et al, 2021;Otto & Mamatoglu, 2015;Wang et al, 2015), there is no in-depth analysis of the role of professional identity and emotional labour in the relationship, especially for clinical nurses. Therefore, the present study aimed to examine the relationship among nurses' perceived organisational justice, professional identity, emotional labour and job performance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, regarding the role of organizational justice, Wang et al (2015) have found that organizational justice plays a moderating role in the relationship between job insecurity and job performance. Similarly, De Angelis et al (2021) have provided support to the role of organizational justice in decreasing the association between job insecurity and job performance among employees of an Italian multiservice social cooperative. In addition, it is necessary to mention that, as participation occurred in a work context, it would be possible that participants were less frank than they would have been in another context.…”
Section: Discussionmentioning
confidence: 91%
“…At the worker level, millions of jobs were lost because of the pandemic (International Labour Organization, 2020 ). It not only impacted job insecurity but also affected emotional and mental health conditions (Lin, Shao, Li, Guo, & Zhan, 2021 ; Obrenovic, Du, Godinic, Baslom, & Tsoy, 2021 ), job performance (De Angelis, Mazzetti, & Guglielmi, 2021 ) and well-being (Stankevičiūtė, Sanchez-Hernandez, & Staniškienė, 2021 ). At the policy level, immediate action at the beginning of the pandemic was related to preventing the COVID-19 from spreading by applying for WFH, which has brought a different way of working (Hartner-Tiefenthaler, Goisauf, Gerdenitsch, & Koeszegi, 2021 ).…”
Section: Discussionmentioning
confidence: 99%